Labour demand adjustment: Does foreign ownership matter? - Emmanuel Dhyne; Catherine Fuss; Claude Mathieu (National Bank of Belgium, 2010)
This paper examines whether multinational companies differ in their employment adjustment from domestic firms, on the basis of a panel of Belgian firms for the period 1997-2007. We focus on incumbent firms as, in general, they account for the largest fraction of net employment creation, especially among multinational firms (MNFs). We obtain structural estimates of adjustment cost parameters for blue-collar workers and white-collar workers, domestic firms, and MNFs. We find evidence of convex, asymmetric (in the sense that it is more expensive to downsize than to upsize) and cross adjustment costs (indicating costly substitution between workers). To adjust white-collar employment seems to be around half as costly for MNFs as for domestic firms. There is no difference between Belgian MNFs and foreign MNFs. A small fraction of the gap between the adjustment costs of MNFs and domestic firms may be explained by the use of fixed-term contracts and early retirement. Controlling for firm size does not yield robust conclusions; the cost advantage of MNFs may diminish, vanish or turn into a disadvantage.
Keywords: 330; Arbeitsnachfrage; Multinationales Unternehmen; Anpassungskosten; Angestellte; Arbeiter; Belgien